The effect of the human cumulus cells-conditioned medium on in vitro maturation of mouse oocyte: An experimental study - Maryam Adib; Seyed Morteza Seifati; Mahmood Dehghani Ashkezari; Arezoo Khoradmehr; Roshan Rezaee-R; Somayyeh Sadat Tahajjodi; Behrouz Aflatoonian (Shahid Sadoughi University of Medical Sciences, 2020)
Background: To increase the results of infertility treatment, many efforts have been made to improve the treatment methods. As assisted reproductive technology is mainly using cell culture methods, one of the approaches to improve this technology is conditioned medium from different sources. It is desirable to apply in vitro maturation (IVM) and use oocytes from normal cycles instead of stimulating ovulation. Objective: To investigate the effect of human cumulus cell condition medium (hCCCM) on the IVM of immature mouse oocytes and morphology. Materials and Methods: In this experimental study, 240 germinal vesile oocytes were collected from four-six wk-old mice after 48 hr of 5IU pregnant mare serum gonadotropin (PMSG) injection and cultured in hCCCM (test group, n = 120) and DMEM + 20% FBS (control group, n = 120). The IVM rates and changes in perivitelline space (PVS) and shape were investigated at 8, 16, and 24 hr following the culture. The mature (MII) oocytes were subjected to in vitro fertilization (IVF) and the fertilization rate was assessed in three days. Results: A significant difference was observed between the maturation rates in the hCCCM and control groups (24.16% vs 0%; p = 0.001), as well as morphologic changes between the two groups (p = 0.04, p = 0.05). The development rate for MII oocytes attained from IVM in the hCCCM group was 27.58% (2-cell) and 6.89% (4-cell). Data displayed that hCCCM is an effective medium for oocytes maturation compared to the control medium. Conclusion: hCCCM supports oocyte in vitro growth and maturation. Moreover, hCCCM changes the oocyte shape and size of perivitelline space.